Stunting in Toddlers: Exploring Multiple Factors Through a Case Control Study - I Kadek Wartana; Veni Mornalita Kolupe; Rizkya Mutohharoh; Sitti Fajrah (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting is a serious concern for children globally, including in Indonesia, often caused by ongoing malnutrition problems. There are numerous factors associated with stunting. This research aims to analysed multiple factors related to stunting in toddlers. Methods: This research utilized a case-control approach. The research was conducted in the Marawola District from Juni to August 2024. A group of 128 toddlers were part of the study, with half of them classified as cases and the remaining half as controls. Variables in this research included maternal characteristics (education, occupation), toilet ownership, exclusive breastfeeding practice, complete immunization, and stunting. Data was collected using questionnaires and direct measurements (anthropometry). Data analysis involved univariate and bivariate analysis using the chi-square test, as well as multivariate analysis using linear regression with 95% confidence interval (CI). Results: The results from the research were indicated a strong correlation between education (p = 0.038), exclusive breastfeeding (p = 0.012), and complete immunization (p = 0.008) with the occurrence of stunting. In particular, it was identified that complete immunization has the highest impact on stunting compared to the others variables studied. Conclusion: A significant association was observed between education, exclusive breastfeeding, complete immunization, and the likelihood of stunting in toddlers. It is crucial to introduce targeted interventions that prioritize the provorsion of proper nutrition, education, and enhanced healthcare accessibility to reduce the prevalence of stunting among toddlers.